Humbertacalia madagascarensis sp. nov. (Asteraceae: Senecioneae) from Madagascar - Peng, Yu-Lan; Zhang, Li-Bing (Phytotaxa, 2016)
A new species of Humbertacalia in the tribe Senecioneae (Asteraceae), H. madagascarensis, from Antsiranana, northern Madagascar, is described and illustrated. This new species is similar to H. voluta in having brown tomentum and short peduncles but is different from the latter in having much longer and coriaceous involucres, larger coriaceous and abaxially purple leaves, leaf blade elliptic, cuneate and oblique at base, and yellowish pappus. This new species is endemic to Madagascar.